ANALISIS PERBANDINGAN KINERJA WAKTU DAN BIAYA PROYEK MENGGUNAKAN METODE EARNED VALUE ANALYSIS (Studi Kasus : Kinerja Kontraktor Proyek Pekerjaan Jalan) - Ristanto, Iwan; Ayu Septiana, Dellia; Agung Wibawa, Satria (Inisiasi, 2025)
The purpose of this study is to determine the comparison of contractors' time and cost performance using the Earned Value Analysis method. The required data include general project data, Project RAB, S-Curve, and Weekly Reports. The results of the study indicate that the performance of contractors in the Wonogiri and Surakarta areas has a positive SV value, meaning the project is running faster than the planned schedule, while the SPI (Schedule Performance Index) value is above 1, this indicates that they are able to complete the project in a more efficient time compared to the plan. Meanwhile, the performance of contractors in the Karanganyar area shows a negative SV value, meaning the project is experiencing delays where the work completed is less than the initial plan. The SPI (Schedule Performance Index) value in the Karanganyar area is equal to 1, this indicates that even though the project is experiencing delays, there is room for improvement in the efficiency of work completion.